2021
DOI: 10.1038/s41598-021-94116-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-513b-5p targets COL1A1 and COL1A2 associated with the formation and rupture of intracranial aneurysm

Abstract: Collagen-type I alpha 1 chain (COL1A1) and COL1A2 are abnormally expressed in intracranial aneurysm (IA), but their mechanism of action remains unclear. This study was performed to investigate the mechanism of COL1A1 and COL1A2 affecting the occurrence and rupture of IA. Quantitative real-time polymerase chain reaction was used to measure the expression of hsa-miR-513b-5p, COL1A1, COL1A2, TNF-α, IL-6, MMP2, MMP3, MMP9 and TIMP4 in patients with ruptured IA (RA) (n = 100), patients with un-ruptured IA (UA) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Target pathways for miR-513b-5p do not appear to overlap with the remainder of the interaction network and include regulation of DNA-binding transcription factor activity as well as RNA biosynthesis. However, miR-513b-5p was recently shown to directly target Collagen type I alpha 1 chain (COL1A1) and COL1A2 to inhibit matrix metalloproteinase (MMP) pathways, thereby enhancing vascular smooth muscle cell death, apoptosis, inflammation and extracellular matrix destruction [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Target pathways for miR-513b-5p do not appear to overlap with the remainder of the interaction network and include regulation of DNA-binding transcription factor activity as well as RNA biosynthesis. However, miR-513b-5p was recently shown to directly target Collagen type I alpha 1 chain (COL1A1) and COL1A2 to inhibit matrix metalloproteinase (MMP) pathways, thereby enhancing vascular smooth muscle cell death, apoptosis, inflammation and extracellular matrix destruction [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Downregulation of miR-513b-5p provided one of the strongest signals in our study. Interestingly, Zheng et al [ 28 ] recently demonstrated that serum levels of miR-513b-5p were significantly decreased in patients with ruptured intracranial aneurysms compared to controls. COL1A1 and COL1A2 were shown to be direct targets of miR-513b-5p in patients with intracranial aneurysms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COL1A1 expression diminished by miR-513b-5p affects the viability of vascular smooth muscle cells. This process might involve the formation and rupture of the intracranial Sirtuin 6 (silencing information regulatory protein 6, SIRT6), a member of the sirtuin family proteins [ 18 ], which regulates collagen metabolism and is an established anti-ageing protein. miR-128 inhibits osteoblast differentiation in osteoporosis by downregulating SIRT6 expression, thus accelerating the development of osteoporosis [ 19 ].…”
Section: Collagen Formationmentioning
confidence: 99%
“…The functions affected include cell proliferation, differentiation, apoptosis, and disease onset and progression ( Bartel, 2004 ; Zhang et al, 2019 ; Wittstatt et al, 2020 ). MiRNA-29a controls the mitochondrial apoptotic pathway, while miRNA-513b-5p targets the COL1A1 and COL1A2 proteins involved in IA formation and rupture ( Zhao et al, 2018 ; Zheng et al, 2021 ). The lncRNAs are more than 200 nucleotides in length but do not have protein-coding capacity ( Wilusz, 2016 ).…”
Section: Introductionmentioning
confidence: 99%